Nd-Fe-B MELT - SPUN POWDER QUALITY ESTIMATION BASED ON STONER - WOHLFARTH MODEL - TAKATA, M.; VUONG, NGUYEN VAN; THUY, DOAN MINH; HIEU, NGUYEN TRUNG; TU, LE TUAN (Communications in Physics, 2007)
The squareness factor, defined as the ratio BH c / i H c , plays very importance role. This factor reflects the magnetization process under a reversed magnetic field in magnet. So the factor can be used as the critical parameter for estimating the magnet quality. For the powder compaction of 6.48 g/cm 3 mass density, if is less than 0.48 then the preparation conditions were far from the optimal ones. The value higher than 0.48 of factor proves that in prepared powder the coupling between grains is enhanced. From the theory and the experiments it was proved that for full dense compaction of NdFeB Stoner-Wohlfarth particles the squareness factor and the maximum energy product(BH)max can not be lager than 0.53 and 10.7 MG. Oe, respectively